Characterization of the gut micro biota in Koreans and investigation of its association with probiotic consumption: implications for microbial ecology and host health - Uh, Yo-Ram; Park, Si-Nae; Song, Min-Jung (Frontiers in Microbiology, 2026)
IntroductionThe gut micro biota is reportedly closely related to human health, and its composition and diversity are determined by a variety of factors, including age, diet, and probiotic intake. Although many studies on the gut micro biota have been conducted, most have focused on Western populations or have been limited by small sample sizes, making it difficult to understand micro biota differences across populations and lifestyles. In this study, we analyzed a large Korean cohort of 3,450 individuals, focusing on gut micro biome differences according to age and host-related markers, as well as the impact of probiotic supplementation.MethodsFecal samples from 3,450 Koreans were analyzed using 16S rRNA gene sequencing (V3–V4 region). Bioinformatics and taxonomic analyses were performed to compare microbial composition and diversity according to age and probiotic intake.ResultsThe data revealed a significant increase in microbial diversity with age and distinct shifts in taxonomic composition between younger and older participants. In addition, probiotic intake did not alter overall community diversity but increased the detection of probiotics, suggesting that they serve as moderators rather than direct drivers of diversity.ConclusionThese findings emphasize the importance of population-specific micro biome research and suggest that diverse host-related and lifestyle factors jointly contribute to shaping gut microbial ecology in Koreans. Probiotic supplementation primarily increased the detection of specific lactic acid bacteria and bifidobacterial species without substantially altering overall alpha diversity, consistent with a modulatory role on targeted taxa rather than broad community restructuring. Together, these results provide a useful framework for future studies linking probiotic-responsive microbial features to human health outcomes and for developing precision nutrition and probiotic strategies in Korean and similar populations.